(3HRhZ GdHOQ aj GdcdGe Ydi HYV aVGFd djdI GdbOQs - (3GdHQOjSj, GdeGdcj, eMeO CUjd GdCfUGQjs
(3ChdgG (B:s
(3hHg fSJYjf hGdUdGI hGdSdGe Ydi SjOfG eMeO hBdg hUMHg hSde, jbhd GdYHO GdNbjQ GdPdjd GdabjQhHYOagPG JYdjb dWja eTJed Ydi ahGFO dWjaI hegeGJ TQjaI hZQGFH efjaIs
(3BNQgG (B:s
(3hCf jYJbfG aj gPg GddjdI ef GdfGQ hjeJYfG HGdfXQ Edi hLgg GdcQje aj OGQ GdbQGQ hCf jOje YdjfG fYeI GdESdGe hCf jMTQfG aj ReQI NjQ GdCfGe hCf jSJYedfG ajeG jQVGg hCf dG jLYdfG ef Cgd GdcSd hGdJdGgs
(3GfJgi GdeDda ef cJGHI GdQSGdI aj CMO CjGe GdYTQ GdCNjQ ef QeVGf SfI (B1092(3g` , hgPg fSNI efbhdI YfgG SfI (B1092(3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs